Comparative analysis of coaches' perception of their capability, opportunity, and motivation to train athletes with special educational needs - Olesia Shevchuk; Iryna Kohut; Viktoriia Marynych (Слобожанський науково-спортивний вісник)
Background: In ensuring equal opportunities for all athletes, including those with special educational needs (SEN), coaches play a key role, as their inclusive competence determines the creation of an inclusive sports environment and affects the quality of the training process. Previous studies using the COM-B model have shown that Ukrainian coaches rate their readiness to train athletes with SEN low. Since this depends on various factors, it is important to understand how different socio-demographic characteristics may influence their responses and behavior.